The Missing Link. Bicycle Infrastructure Networks and Ridership in 74 US Cities. - Schoner, Jessica E.; Levinson, David M. (My University, 2014)
Cities promote strong bicycle networks to support and encourage bicycle commuting. However, the application of network science to bicycle facilities is not very well studied. Previous work has found relationships between the amount of bicycle infrastructure in a city and aggregate bicycle ridership, and between microscopic network structure and individual tripmaking patterns. This study fills the missing link between these two bodies of literature by developing a standard methodology for measuring bicycle facility network quality at the macroscopic level and testing its association with bicycle commuting. Bicycle infrastructure maps were collected for 74 United States cities and systematically analyzed to evaluate their network structure. Linear regression models revealed that connectivity and directness are important factors in predicting bicycle commuting after controlling for demographic variables and the size of the city. These findings provide a framework for transportation planners and policymakers to evaluate their local bicycle facility networks and set regional priorities that support nonmotorized travel behavior, and for continued research on the structure and quality of bicycle infrastructure and behavior.
Keywords: Individualverkehr; Pendlerverkehr; Fahrradverkehr; Verkehrsinfrastruktur; Radwegenetz; Verkehrsplanung; Verkehrsverhalten; Fahrradinfrastruktur; Radverkehrsnetz; Mobilitätsverhalten; Vernetzung